Positivisme dan Non-Positivisme dalam Jurisprudensi - Biyanto, Biyanto (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This article discusses about trend positivism and non-positivism paradigm in jurisprudence. This topic is important because discourse in social philosophy always relies on the rationality of whole arguments. The argument of justification is preceded through deductive reasoning, starting from paradigmatic premise that will be used to justify conclusion. Paradigmatic premise is the basic principles of truth which is believed to be the real truth. The real truth derives from personal experience in reflecting facts found in daily activities. In contemporary context of jurisprudence, there is a fierce battle between legal profesionals with its positivist paradigm (legal or formal law approach) and legal profesionals with its non-positivistic paradigm (legal morale substance approach). Many critics on positivism were responded by efforts to reform law through social movements. Social realist movement derives from diverse reality of socio-cultural configuration, within national life, will be significant when the movement is massively done, and supported by two pilars of civil society and political power. This opposition movement shall be continuously done to against the established side. The well established community has authority upon whole legal institution and usually will utilize all its power structures in order to maintain their interest.